1978
DOI: 10.1144/gsjgs.135.4.0389
|View full text |Cite
|
Sign up to set email alerts
|

Metallogenesis in the Japanese island arc system

Abstract: Ore deposits in the Mesozoic and Cenozoic orogenic belts of the Japanese island arc system consist essentially of stratabound, vein and skarn types. The stratabound base-metal deposits, which are the main source of copper, are divided into the lead-free, chalcopyrite-pyrite, Besshi-type, which occur mainly in glaucophane schists (metamorphosed basaltic pyro-clastic rocks) of the Sanbagawa belt, and the lead-bearing, polymetallic, massive sulphide, Kuroko-type, associated with rhyolite extrusion. Both types are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…In conclusion, the previous results by SHIBATA and ISHIHARA (1974), YAMAOKA and UEDA (1974), ISHIHARA (1978) and newly obtained data show that in the W Province, the base metal mineralization such as associated with Cu occurred later than the major tungsten mineralization, but somewhat earlier than the precious metal mineralization and the base and precious metal mineralization in and around the Ikuno-Akenobe Province.…”
Section: Yabu Mine (Hyogo Prefecture)supporting
confidence: 61%
“…In conclusion, the previous results by SHIBATA and ISHIHARA (1974), YAMAOKA and UEDA (1974), ISHIHARA (1978) and newly obtained data show that in the W Province, the base metal mineralization such as associated with Cu occurred later than the major tungsten mineralization, but somewhat earlier than the precious metal mineralization and the base and precious metal mineralization in and around the Ikuno-Akenobe Province.…”
Section: Yabu Mine (Hyogo Prefecture)supporting
confidence: 61%
“…These deposits were considered to have formed syngenetically in relation to submarine volcanism in geosynclinal belts (e.g. Tatsumi et al, 1970;Watanabe et al, 1970a;Ishihara, 1978). However, microbiostratigraphic and tectonic studies (Isozaki et al, 1990;Isozaki and Maruyama, 1991) suggested that the major deposits associated with chert and basalt are of oceanic origin and are allochthonous to the continental margin environment.…”
Section: Discussionmentioning
confidence: 99%
“…The Sn-associated reduced-type felsic magmatism is thought to have been caused by the subduction of the hot back arc basin and the significant crustal melting (Fig. 8) in a similar manner to the Middle Miocene Sn-associated reduced-type granitoid magmatism in the Cretaceous to Paleogene Shimanto accretionary zone of Southwest Japan (e.g., Ishihara, 1978;Ishihara et al, 1992). The Middle Miocene magmatism could have been caused by the interaction of Southwest Japan arc with the very young, and presumably hot, Shikoku Basin due to the opening of Sea of Japan (e.g., Kobayashi and Sato, 1979;Takahashi, 1986;Furukawa and Tatsumi, 1999).…”
Section: Tectonic Model and Related Subject: Proposal Ofmentioning
confidence: 97%